Marriage and health : the well-being of same-sex couples - Liu, Hui, 1977-; Reczek, Corinne E.; Wilkinson, Lindsey, 1982- (Politics of marriage and gender: global issues in local contexts., 2020)
"Studies have shown that married couples have better mental and physical health than unmarried people. Leading scholars and policy makers propose that marriage can provide similar benefits to people in both same-sex and different-sex relationships. Though research on the health and well-being of same-sex couples is a new and growing field, Marriage and Health: The Well-Being of Same-Sex Couples represents the forefront of marriage and health research and the far-reaching policy implications for the health of same-sex couples. This collection of essays presents new perspectives that address current opportunities and challenges faced by people in same-sex unions in multiple domains of well-being, including physical and mental health, social support, socialized behaviors, and stigmas. The book offers a broad view of same-sex couples' experiences by examining not only marriage and civil unions, but also dating and cohabiting relationships as well as same-sex sexual experiences outside of relationships"--